Design method for mix proportion of carbonized 3D printing concrete and carbonized 3D printing concrete
By magnesium ions regulating the crystal form of calcium carbonate and optimizing the proportion of calcium carbonate in aragonite phase, the problems of high admixture usage, large carbon emissions and poor constructionability in 3D printed concrete are solved, and the efficient rheology and strengthening of the material are achieved.
Patent Information
- Application Number
- CN202411640873.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Existing 3D printed concrete technology requires the addition of a large number of admixtures to meet the requirements of thixotropy, resulting in high costs, increased carbon emissions, and incompatible constructability with rheology.
The calcium carbonate crystal form is regulated through magnesium ions to improve the rheological behavior of the material, and the mechanical properties of the material after printing are improved through the relationship between the proportion of calcium carbonate in the aragonite phase and the concentration and temperature of magnesium ion.
It has achieved the reduction of admixture usage, reduced carbon emissions, improved the constructability and rheological properties of the material, and enhanced the mechanical properties of the material after printing.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of 3D concrete printing, regulates the thixotropic behavior of materials through carbonization, and is a design method for a mix ratio of carbonized 3D printing concrete and carbonized 3D printing concrete. Background Art
[0002] In the field of construction, the study of 3D printing technology combined with the industry is the most cutting-edge research direction in the industry to achieve digital and intelligent buildings. In the actual construction printing process, 3D printing concrete technology has high plasticity and does not require support during the molding process. It is a new type of formwork-free concrete molding technology. In the field of 3D printing concrete, a large amount of admixtures need to be added to cement-based slurry to meet the requirements of thixotropy, which is costly.
[0003] Materials are the core of architectural 3D printing, and 3D printed building materials are still mostly cement-based materials, which is the main source of carbon emissions. In the process of producing 3D printed concrete materials, it is not only to reduce carbon emissions and achieve carbon fixation, but also to improve the utilization rate of solid waste and the printing performance of materials. By regulating the crystal form of calcium carbonate and adjusting its rheology, it has become a research hotspot in the field of engineering materials. Summary of the invention
[0004] Based on this, the present invention provides a design method for a carbonized 3D printed concrete mix ratio and carbonized 3D printed concrete to solve the technical problems existing in the prior art, such as the need to add a large amount of admixtures to meet the thixotropy requirements, high cost, increased carbon emissions, and incompatibility between constructability and rheology.
[0005] The present invention utilizes magnesium ions to regulate the crystal form of calcium carbonate to improve the rheological behavior of the material, establishes a relationship between the proportion of aragonite phase calcium carbonate and the magnesium ion concentration and temperature, and proposes a fiber orientation index of aragonite needle-rod-shaped calcium carbonate fibers, which is used to quantitatively improve the mechanical properties of the printed material.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for designing a mix ratio of carbonized 3D printed concrete comprises the following steps:
[0008] 1) Weigh component A, add deionized water to dissolve calcium ions, add admixtures, adjust pH, and react fully to obtain cement-based printing slurry;
[0009] 2) introducing component B into the cement-based printing slurry, controlling the amount of component B introduced, so that the minerals in the cement-based printing slurry react with component B to form carbonates, and while introducing component B into the cement-based printing slurry, calculating the amount of component C according to the content of CaCO3, a carbonization product, and the ratio of calcite to aragonite in the desired concrete mixture, and adding component C and component B into the cement-based printing slurry at the same time to fully react;
[0010] 3) Then, component D is added and stirred thoroughly to obtain a 3D printing concrete material.
[0011] Preferred raw materials of the present invention are:
[0012] According to the present invention, component A is preferably Portland cement clinker.
[0013] According to the preferred embodiment of the present invention, the main mineral components of silicate cement clinker are tricalcium silicate, dicalcium silicate, tricalcium aluminate, and tetracalcium aluminoferrite, and the weight content of tricalcium silicate and dicalcium silicate accounts for 70% to 85%. In the fully hydrated solution, CSH gel accounts for 65-75% of the total volume, and calcium hydroxide accounts for 15-25%. The hydration characteristics of silicate cement clinker are very similar to those of Portland cement. It is called strength mineral.
[0014] According to the preferred embodiment of the present invention, component B is a carbonate source material, and the carbonate source material is air or carbonized gas containing carbon dioxide. The main chemical composition of component B is carbon dioxide, and the treated concrete mixture shows an increase in compressive strength. For OPC mixtures, the compressive strength benefit of concrete samples with a carbon dioxide content of 0.10% is as high as 30%, and during the mixing process, the addition of carbon dioxide significantly affects the durability of the concrete, and has no effect on the pH value of the concrete.
[0015] Preferably according to the present invention, component C is a magnesium chloride solution, the molar concentration of the magnesium chloride solution is 0.1125 mol / L to 0.1375 mol / L, and the ionic strength of magnesium chloride is 3.0.
[0016] Component C is used as a crystal form controller to adjust the crystal form of calcium carbonate to form aragonite. CaCO3 whiskers grow by heterogeneous nucleation with Mg(OH)2 colloidal precipitation as the seed. Mg(OH)2 colloid is adsorbed on the surface of the crystal, inhibiting the transformation of aragonite phase CaCO3 whiskers to calcite phase.
[0017] According to the preferred embodiment of the present invention, component D is a mineral admixture, and the mineral admixture is selected from one or more of fly ash, granulated blast furnace slag, silica fume, lime powder, steel slag powder industrial solid waste. Component D is mainly used to improve the rheological properties, setting time, hardening performance, durability, etc. of the concrete mixture.
[0018] According to the preferred embodiment of the present invention, the admixture is selected from one or a mixture of two or more of water reducer, retarder, air entrainer, pumping agent and rust inhibitor. Water reducer, retarder, air entrainer, pumping agent and rust inhibitor are prepared according to the prior art.
[0019] Calculation method of raw material ratio:
[0020] According to the preferred embodiment of the present invention,
[0021] ① Determination of calcium content
[0022] According to the proportion of calcium in component A, the amount of calcium carbonate generated after the introduction of carbon dioxide is determined, and the calculation method is as follows:
[0023]
[0024] m Ca =(p Ca ·M+n·N)(2)
[0025]
[0026] Where: p Ca is the proportion of calcium in component A; x is the mass of C3S and C2S in component A; k is the proportion of calcium in C3S and C2S in component A; M is the total weight of all materials in component A; n is the proportion of calcium in mineral admixtures; N is the mass of mineral admixtures; m Ca is the total amount of calcium in the product; z is the reaction efficiency, that is, the calcium carbonate production rate; is the amount of calcium carbonate produced.
[0027] ②Determination of magnesium content
[0028] Using magnesium chloride as the crystal form control agent, in the presence of Ca 2+ Under the conditions of concentration 0.5 mol / L, reaction temperature 80°C, stirring rate 200 rpm, and component B flow rate 200 mL / min, the average aspect ratio of the CaCO3 samples prepared at different magnesium chloride addition amounts is shown in the following table
[0029] Table 1 Average aspect ratio of CaCO3 samples prepared at different magnesium chloride addition amounts
[0030]
[0031] The invention determines the reasonable aspect ratio of the calcium carbonate sample through the orientation index of the aragonite needle-rod calcium carbonate fiber.
[0032] The morphological characteristics of the nanofibers themselves have a significant influence on the fiber orientation. The fiber orientation index is used to characterize the orientation of aragonite needle-rod-like calcium carbonate in cement-based materials. The higher the value, the more parallel the fibers are to the printing direction.
[0033] The orientation index obeys the following formula (4):
[0034]
[0035] In the formula, ξ θ is the fiber orientation index (ξ θ ∈(0, 1)); θ is the fiber polar angle; n is the total number of fibers.
[0036] In three-dimensional space, the fiber polar angle refers to the two-dimensional plane angle between the center line of the aragonite needle-shaped calcium carbonate fiber and the printing direction, ranging from 0° to 90°, and the fiber azimuth angle represents the projection position of the fiber in the three-dimensional coordinate system. After calculating the fiber orientation index, the orientation index of the samples with fiber aspect ratios of 6 and 12 were 0.48 and 0.56, respectively.
[0037] Through the aspect ratio analysis of aragonite phase calcium carbonate, it was found that when the nozzle size remained unchanged, increasing the fiber aspect ratio restricted its rotation, that is, increasing the fiber aspect ratio could enhance the arrangement of fibers along the printing direction.
[0038] When the addition amount of magnesium chloride is less than 5%, the CaCO3 sample is mainly in the shape of agglomerated or dispersed spindles. In order to ensure the regularity and more regular arrangement of the morphology of CaCO3 whiskers, the most suitable addition amount of magnesium chloride solution is 5%.
[0039]
[0040] In the formula, The total amount of magnesium chloride solution
[0041] Magnesium chloride with an ionic strength of 3.0 showed promotion of C3S dissolution. Due to the strong solvation effect of a large number of sodium ions and magnesium ions, the solvation degree of calcium ions in C3S crystals was weakened, which reduced the stability of water molecules in the solvation shell of calcium ions. The presence of a large number of background ions accelerated the migration of water molecules near the crystals, thereby promoting the dissolution of calcium ions. At the same time, a large number of magnesium ions also prepared for the subsequent carbonization reaction to adjust the precipitation crystal form.
[0042] The relationship between different temperatures and magnesium chloride solution concentration is shown in Table 2
[0043] Table 2 Relationship between suitable magnesium chloride solution concentration and temperature
[0044]
[0045] As shown in the table, the best condition is when the magnesium chloride concentration is 0.119 mol / L at 80°C.
[0046] ③ Determination of the proportion of aragonite phase
[0047] The thixotropic behavior of the printing slurry can be used as an indicator to evaluate the buildability of the material. The present invention quantifies the thixotropic behavior through the thixotropic index, which can be defined as the ratio of the static yield stress to the dynamic yield stress:
[0048]
[0049] In the formula, I this is the thixotropy index; τ s and τ d are the static yield stress and dynamic yield stress (Pa) at a given shear rate and shear time, respectively.
[0050] Among them, the evolution of static and dynamic yield stress of aragonite phase calcium carbonate with time is usually fitted by a linear regression model:
[0051] τ=(τ0+A this ·t)(7)
[0052] Where τ is the yield stress (Pa); t is the time (s); τ0 is the initial static yield stress at t = 0 (Pa); A this is the structural accumulation rate (Pa / s);
[0053] The fitting results of aragonite phase calcium carbonate are shown in Table 3
[0054] Table 3 Linear regression fitting of yield stress of aragonite phase calcium carbonate over time
[0055]
[0056] Among them, the evolution of static and dynamic yield stress with time under different aragonite phase calcium carbonate ratios is usually fitted by a linear regression model:
[0057] τ1=τ+(1.2hh 2 +1)·A this t (8)
[0059] Wherein, h is the proportion of aragonite phase calcium carbonate. The CaCO3 crystal form is determined by X-ray diffraction (XRD), and the content of aragonite phase calcium carbonate whiskers in the product is calculated by the following formula (9):
[0060]
[0061] Where y is the percentage of aragonite phase, Ia and Ic are the integrated intensities of the strongest characteristic peaks of aragonite phase and calcite phase in the XRD spectrum, respectively, and the diffraction planes are (221) and (104), respectively.
[0062] The relationship between the proportion of calcite phase calcium carbonate in the material and the static and dynamic yield stresses is shown in Table 4. In order to ensure sufficient reaction, t=1800s is taken.
[0063] Table 4 Effect of aragonite proportion on static and dynamic yield stress
[0064]
[0065] A higher influence index is beneficial to 3D printing. For example, 3D printing requires high static yield stress and low dynamic yield stress. As shown in the table above, when the proportion of aragonite phase calcium carbonate is about 50%, the influence index is higher. Compared with the proportion of 60%, a smaller aragonite phase content can achieve better thixotropic behavior, and a greater cost is required when the proportion is 60%, so a 50% aragonite phase calcium carbonate proportion is used.
[0066] According to multiple experiments, combined with the static yield stress and dynamic yield stress of the material, in order to ensure full reaction, the reaction time is controlled at about 30 minutes, and the optimal influence index is defined to be controlled between 19.3 and 19.4. The material at this time has better early fluidity, extrudability, and later constructability. From this, it can be seen that the proportion of aragonite phase calcium carbonate is between 0.4 and 0.6, and it can be concluded that the concentration of magnesium chloride solution is between 0.1125mol / L and 0.1375mol / L. According to the 5% magnesium chloride usage ratio, it can be concluded that the amount of magnesium chloride solution is within the following range:
[0067]
[0068] Among them, under different temperature conditions, the proportion of aragonite phase calcium carbonate changes with the concentration of magnesium chloride solution and obeys the following formula:
[0069]
[0070] Where q is temperature; p is magnesium ion concentration; r is the proportion of aragonite phase calcium carbonate; the value of p0 varies with the proportion of aragonite phase calcium carbonate and follows formula (11).
[0071] According to many conditions such as the ratio of magnesium chloride to sodium hydroxide in the stirring device, based on the carbon dioxide content, according to its introduction rate, the speed of the stirring device, etc., the reaction temperature, the stirring rate, the CO2 flow rate, the preferred conditions of the ratio of magnesium chloride to sodium hydroxide are shown in Table 5.
[0072] Table 5 Optimal conditions
[0073]
[0074]
[0075] Sodium hydroxide is mainly used to control pH, so that aragonite phase calcium carbonate is stably generated.
[0076] According to the data in the table, under the conditions of reaction temperature of 80°C, stirring rate of 200rpm, CO2 flow rate of 200mL / min, and ratio of magnesium chloride to sodium hydroxide of 2.6, the calcite phase calcium carbonate in the product accounts for about 51.03%, so that the product produces a higher yield stress in static state and a lower yield stress in dynamic state, achieving better thixotropic behavior and thus realizing stronger constructability.
[0077] A carbonized 3D printing concrete is obtained by adopting the above method.
[0078] The above-mentioned carbonized 3D printed concrete is used in 3D printed buildings.
[0079] The above-mentioned carbonized 3D printing concrete mix ratio design method is carried out in a 3D printing concrete device, which includes a mixing tank, a concrete mixer, a carbon dioxide gas tank, and a magnesium chloride container. The concrete mixer, the carbon dioxide gas tank, and the magnesium chloride container are connected to the mixing tank through a hose, and the bottom end of the mixing tank is connected to a concrete 3D printing nozzle.
[0080] The mixing tank is the main place for carbonization reaction, which mainly consumes carbon dioxide and generates nano-scale calcium carbonate precipitation. The temperature of the mixing tank is controlled at about 80°C, the gas flow rate is controlled at 200ml / min, and mechanical stirring is started at a stirring speed of 200r / min. After sufficient stirring.
[0081] The concrete mixer has a pumping function and is used to prepare cement-based printing slurry and complete the slurry pumping. A temperature regulator is provided in the mixer to maintain the temperature of the reactants in step 1) at about 80°C. A pH monitor is also provided to observe the pH changes of the solution in real time to control the acidity and alkalinity of the reaction solution.
[0082] Carbon dioxide gas cylinders are used to store carbonate source materials, which are carbonized gases containing carbon dioxide and come from many sources such as factory exhaust gas or vehicle exhaust gas.
[0083] The magnesium chloride container is used to store magnesium chloride solution. In the early stage of the magnesium chloride solution, magnesium ions promote the dissolution of C3S and C2S, and in the later stage, magnesium chloride adjusts the crystal form of calcium carbonate precipitation.
[0084] The technical features and advantages of the present invention are as follows:
[0085] 1. To improve the buildability of printed materials, thixotropic behavior is used to characterize and quantify using a thixotropic index. The present invention studies different proportions of aragonite phase calcium carbonate and calcite phase calcium carbonate. Due to the regular needle-like structure of aragonite phase calcium carbonate, it can be arranged along the shear direction during the shearing process, thereby generating a higher yield stress in static state and a lower yield stress in dynamic state, which has a positive effect on the thixotropic behavior of the material.
[0086] 2. In order to accurately calculate and control the amount of aragonite phase calcium carbonate generated, the present invention studies and analyzes the reasonable concentration and dosage of magnesium chloride solution, and determines the reasonable ratio of sodium hydroxide to magnesium chloride solution to regulate the amount of aragonite phase calcium carbonate generated.
[0087] 3. The present invention forms carbonate reaction products in situ by adding gaseous CO2 to the newly stirred concrete, i.e., nanoscale and uniformly distributed calcium carbonate precipitation, and produces an appropriate amount of aragonite phase calcium carbonate through the action of magnesium chloride, so that the cement slurry has stronger constructability. Due to the needle-rod-shaped nanoscale fiber structure of aragonite phase calcium carbonate, under the flow action of conveying cement-based materials and the extrusion action of the print head, the orientation of the nanoscale aragonite fibers is arranged in the printing direction, i.e., the flow direction, and has excellent strengthening and toughening effects, and the flexural, bending and compressive strengths are all improved.
[0088] 4. Magnesium chloride can significantly improve the early mechanical properties of aragonite whiskers, make the pore structure finer, and significantly improve the compressive strength and flexural strength. The generation of aragonite calcium carbonate reduces the calcium hydroxide orientation index of cement, reduces the growth space of calcium hydroxide crystals, and improves the structural density of cement paste. Aragonite can also be used as a filler for ultrafine fibers and cementitious composite materials. These effects improve the microstructure of cement paste, thereby improving the flexural and compressive strength of cement paste. The present invention improves the flexural and compressive strength of cement paste by adding magnesium chloride and generating aragonite calcium carbonate. BRIEF DESCRIPTION OF THE DRAWINGS
[0089] Figure 1 Schematic diagram of the carbonization principle of concrete.
[0090] Figure 2 This is a structural schematic diagram of a 3D printing concrete device, including: 1. a concrete mixer; 2. a magnesium chloride container; 3. a pH monitor; 4. a mixing tank; 5. a 3D printing nozzle; 6. a flow meter; and 7. a carbon dioxide gas tank. DETAILED DESCRIPTION
[0091] The technical solutions in the present invention are described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The raw materials used in the embodiments are all conventional raw materials and can be obtained commercially; the methods described are all prior art unless otherwise specified. Based on the embodiments in the present invention, all other examples improved or modified by ordinary technicians in the field belong to the scope of protection of the present invention.
[0092] The structure of the 3D printing concrete device in the embodiment is as follows Figure 2 As shown, it includes a mixing tank, a concrete mixer, a carbon dioxide gas tank, and a magnesium chloride container. The concrete mixer, the carbon dioxide gas tank, and the magnesium chloride container are connected to the mixing tank through a hose, and the bottom end of the mixing tank is connected to a concrete 3D printing nozzle.
[0093] Example 1
[0094] A design method for a carbonized 3D printed concrete mix ratio, the steps are as follows:
[0095] 1) Weigh component A silicate cement clinker, add deionized water to dissolve calcium ions, add a water reducer, adjust the pH with sodium hydroxide, and react fully to obtain a cement-based printing slurry;
[0096] 2) introducing air into the cement-based printing slurry, controlling the amount of air introduced, so that the minerals in the cement-based printing slurry react with the air to form carbonates, and while introducing air into the cement-based printing slurry, calculating the amount of magnesium chloride solution according to the content of CaCO3, a carbonization product, and the ratio of calcite to aragonite in the desired concrete mixture, and adding the magnesium chloride solution and air into the cement-based printing slurry at the same time for sufficient reaction;
[0097] 3) Then add fly ash and stir thoroughly to obtain 3D printing concrete material.
[0098] ① Determination of calcium content
[0099] According to the proportion of calcium in component A, the amount of calcium carbonate generated after the introduction of carbon dioxide is determined, and the calculation method is as follows:
[0100]
[0101] m Ca =(p Ca ·M+n·N)(2)
[0102]
[0103] Where: p Cais the proportion of calcium in component A; x is the mass of C3S and C2S in component A; k is the proportion of calcium in C3S and C2S in component A; M is the total weight of all materials in component A; n is the proportion of calcium in mineral admixtures; N is the mass of mineral admixtures; m Ca is the total amount of calcium in the product; z is the reaction efficiency, that is, the calcium carbonate production rate; is the amount of calcium carbonate produced.
[0104] Combined with the static yield stress and dynamic yield stress of the material, in order to ensure sufficient reaction, the reaction time is controlled to about 30 minutes, and the optimal influence index is defined to be controlled between 19.3 and 19.4. At this time, the material has better early fluidity, extrudability, and later constructability. Therefore, it can be seen that the proportion of aragonite phase calcium carbonate is between 0.4 and 0.6, and it can be concluded that the concentration of magnesium chloride solution is between 0.1125mol / L and 0.1375mol / L. According to the 5% magnesium chloride usage ratio, it can be concluded that the amount of magnesium chloride solution is within the following range:
[0105]
[0106] Among them, under different temperature conditions, the proportion of aragonite phase calcium carbonate changes with the concentration of magnesium chloride solution and obeys the following formula:
[0107]
[0108] Where q is temperature; p is magnesium ion concentration; r is the proportion of aragonite phase calcium carbonate; the value of p0 varies with the proportion of aragonite phase calcium carbonate and follows formula (11).
[0109] According to many conditions such as the ratio of magnesium chloride to sodium hydroxide in the stirring device, the preferred conditions for the ratio of magnesium chloride to sodium hydroxide based on carbon dioxide content, reaction temperature, stirring rate, CO2 flow rate are shown in Table 5.
[0110] Table 5 Optimal conditions
[0111]
[0112] Sodium hydroxide is mainly used to control pH, so that aragonite phase calcium carbonate is stably generated.
[0113] According to the data in the table, under the conditions of reaction temperature of 80°C, stirring rate of 200rpm, CO2 flow rate of 200mL / min, and ratio of magnesium chloride to sodium hydroxide of 2.6, the calcite phase calcium carbonate in the product accounts for about 51.03%, so that the product produces a higher yield stress in static state and a lower yield stress in dynamic state, achieving better thixotropic behavior and thus realizing stronger constructability.
[0114] Example 2
[0115] A carbonized 3D printing concrete is prepared according to the method of Example 1.
Claims
1. A method for designing a mix ratio of carbonized 3D printed concrete, comprising the following steps: 1) Weigh component A, add deionized water to dissolve calcium ions, add admixtures, adjust pH, and react fully to obtain cement-based printing slurry; 2) introducing component B into the cement-based printing slurry, controlling the amount of component B introduced, so that the minerals in the cement-based printing slurry react with component B to form carbonates, and while introducing component B into the cement-based printing slurry, calculating the amount of component C according to the content of CaCO3, a carbonization product, and the ratio of calcite to aragonite in the desired concrete mixture, and adding component C and component B into the cement-based printing slurry at the same time to fully react; 3) Then, component D is added and stirred thoroughly to obtain a 3D printing concrete material.
2. The method according to claim 1, characterized in that Component A is silicate cement clinker. The main mineral components of silicate cement clinker are tricalcium silicate, dicalcium silicate, tricalcium aluminate and tetracalcium aluminoferrate. The weight content of tricalcium silicate and dicalcium silicate accounts for 70% to 85%. In the fully hydrated solution, CSH gel accounts for 65-75% of the total volume, and calcium hydroxide accounts for 15-25%. The hydration characteristics of silicate cement clinker are very similar to those of Portland cement.
3. The method according to claim 1, characterized in that Component B is a carbonate source material, and the carbonate source material is air or a carbonized gas containing carbon dioxide.
4. The method according to claim 1, characterized in that: Component C is a magnesium chloride solution, the molar concentration of the magnesium chloride solution is 0.1125 mol / L to 0.1375 mol / L, and the ionic strength of the magnesium chloride is 3.
0.
5. The method according to claim 1, characterized in that: Component D is a mineral admixture, which is selected from one or more of fly ash, granulated blast furnace slag, silica fume, lime powder, and steel slag powder industrial solid waste, and the admixture is selected from one or more of a water reducer, a retarder, an air entraining agent, a pumping agent, and a rust inhibitor.
6. The method according to claim 1, characterized in that The calculation method of raw material ratio is as follows: Calcium content determination According to the proportion of calcium in component A, the amount of calcium carbonate generated after the introduction of carbon dioxide is determined, and the calculation method is as follows: m Ca =(p Ca ·M+n·N)(2) Where: p Ca is the proportion of calcium in component A; x is the mass of C3S and C2S in component A; k is the proportion of calcium in C3S and C2S in component A; M is the total weight of all materials in component A; n is the proportion of calcium in mineral admixtures; N is the mass of mineral admixtures; m Ca is the total amount of calcium in the product; z is the reaction efficiency, that is, the calcium carbonate production rate; is the amount of calcium carbonate produced.
7. The method according to claim 1, characterized in that The calculation method of raw material ratio is as follows: Magnesium content determination The concentration of magnesium chloride solution is between 0.1125mol / L and 0.1375mol / L. According to the magnesium chloride usage ratio of 5%, the dosage of magnesium chloride solution is within the following range: Among them, under different temperature conditions, the proportion of aragonite phase calcium carbonate changes with the concentration of magnesium chloride solution and obeys the following formula: Where q is temperature; p is magnesium ion concentration; r is the proportion of aragonite phase calcium carbonate; the value of p0 varies with the proportion of aragonite phase calcium carbonate and follows formula (11).
8. The method according to claim 1, characterized in that The reaction temperature, stirring rate, CO2 flow rate, and ratio of magnesium chloride to sodium hydroxide are as follows: Sodium hydroxide is mainly used to control pH so that aragonite phase calcium carbonate is stably generated.
9. A carbonized 3D printing concrete, prepared by the method according to any one of claims 1 to 8.
10. Use of the carbonized 3D printing concrete according to claim 9 in 3D printing buildings.
Citation Information
Patent Citations
Method for fixing carbon dioxide by using silicon-calcium-based solid waste and application thereof
CN115073126A
Method for capturing CO2 by calcium silicate and synchronously condensing into high-breaking-strength material
CN115536321A
3D printing concrete material as well as preparation method and application thereof
CN116589246A
Method for preparing reactive artificial sand based on red mud reinforced steel slag accelerated carbonization
CN116874217A
Method for manufacturing aragonite type calcium carbonate
JP2001354416A
Cited By
Concrete doped with solid waste fibers and preparation method thereof
CN120058317A
Dynamic carbon injection recycled coarse aggregate concrete as well as preparation method and application thereof
CN121248211A
Super-hydrophobic mortar based on carbonized fly ash as well as preparation method and application of super-hydrophobic mortar
CN121405421A